Transgressing Professional Boundaries through Fat and Disabled Embodiments - Rice, Carla; Bessey, Meredith; Roosen, Kaley; Kirkham, Andrea (Canadian Woman Studies/les cahiers de la femme, 2023)
We mine our experiences of fatness and disability to argue that professional doctrines function as professional biopedagogies: implicit and explicit instructions that teach us all how to manage our (professional) bodies through morally “right” behaviours. Analyzing our bodily transgressions leads to new insights about ways those in the “caring” professions might re-imagine our work, ourselves, and our practices.